Have Some Signatories of a Covid-19 Literature Open Access Agreement Reneged on Their Promise? - Teixeira da Silva, Jaime A.; Okagbue, Hilary I. (Universitas Pendidikan Indonesia, 2022)
Coronavirus disease 2019 (COVID-19) is one of humanity’s greatest modern socio-medical challenges. Cognizant of the serious nature of this pandemic, and before it was characterized as such, the Wellcome Trust in the UK took the bold and important initiative to call on publishers to make any research related to COVID-19 open access (OA) and encourage them to adopt open data (OD) policies. In a public statement, many publishers of subscription-based and OA journals agreed that all literature related to COVID-19 would be OA as a service to the public, society and humanity. Despite that stated agreement, evidence indicates that not all literature pertaining to this pandemic or virus is OA. In thus study, Web of Science data (August 4, 2021) indicates that 83.7% of 2020 COVID-19-related literature (78.4% for 2021; average of 81.2%) is OA, i.e., an average of 19.8% in 2020 and 2021 was not OA. It is not clear why that literature is not OA. Signatories of that Wellcome Trust-coordinated statement should offer a public explanation, or abandon being signatories.